2020
DOI: 10.14202/vetworld.2020.2618-2624
|View full text |Cite
|
Sign up to set email alerts
|

Sero-epidemiological study on Dengue fever virus in humans and camels at Upper Egypt

Abstract: Background and Aim: Dengue fever (DF) is an important mosquito-borne viral zoonosis affecting over 100 countries worldwide and putting about 3.9 billion people at risk of infection. The disease has re-emerged in Egypt since 2011; however, there is a paucity of recent epidemiological data available. Therefore, in this study, we employed a cross-sectional study to determine DF prevalence in humans and camels in Asyut and Sohag Governorates, Egypt, during 2019. Materials and Methods: A total of 91 humans and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This gap in the literature has existed for half a century. In Sohag and Assiut in 2019, the positive rates of DENV antibodies in the general population aged <21 years, 21 to 40 years, and >40 years old were 25%, 11.32%, and 10%, respectively, and 3.30% in local camels [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This gap in the literature has existed for half a century. In Sohag and Assiut in 2019, the positive rates of DENV antibodies in the general population aged <21 years, 21 to 40 years, and >40 years old were 25%, 11.32%, and 10%, respectively, and 3.30% in local camels [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies on DENV seroprevalence in the Red Sea region and Pakistan have indicated a rate of more than 20% DENV seroprevalence in the general population [ 23 ]. Moreover, DENV has been prevalent in camels in Egypt, with an antibody positivity rate of 3.3% [ 34 ], implying that camels may serve as reservoirs of DENV. The seropositivity rate for DENV was 47.6% among residents from El-Gadarif State, Sudan [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the prevalence among the general population in some cities in Upper Egypt, where outbreaks of dengue have been previously reported, was found to be 12.09%. 16 Using an alpha error = 5% and a precision = 3%, the minimum required sample size was found to be 454, and we eventually enrolled 500 participants. The sample size was calculated using Epi-Info software (version 7).…”
Section: Methodsmentioning
confidence: 99%
“…As was expected, coinfections between tropical pathogens and COVID-19 are also now increasingly being reported, especially with dengue (30). Dengue affects over 100 countries worldwide and puts about 2.5-3.9 billion people at risk of infection (113,114). Within the next century, nearly a billion people are at risk of exposure to virus transmission by both main Aedes spp., Ae.…”
mentioning
confidence: 88%